One Health messaging about bats and rabies: how framing of risks, benefits and attributions can support public health and wildlife conservation goals - Lu, Hang; McComas, Katherine A.; Buttke, Danielle E.; Roh, Sungjong; Wild, Margaret A.; Decker, Daniel J. (Wildlife research (East Melbourne), 2017)
Context. Improving awareness to prevent exposure to rabies from bats is a public health priority. However, messages about bats and rabies often sensationalise this issue and represent bats in a negative way, which can negatively affect support for bat conservation. Aims. The conflicts between public health goals and conservation needs seem unavoidable but are not irreconcilable. Natural resource managers and public health officials can work together to ensure that the importance of preventing exposure to rabies from bats is effectively communicated while at the same time promoting public appreciation of bat species. One efficacious way of achieving this communication goal may be through careful design of message content. This study aims to evaluate the efficacy of message design strategies in promoting rabies prevention and bat conservation. Methods. This study tested messages in two USA National Park Service sites. Participants (n = 480) were randomly assigned to one of four message conditions as part of a 2 (risk–benefit vs risk-only of bats) × 2 (human blame vs bat blame for disease) between-subjects factorial design, or to a control (no message) condition. Key results. The results show that all four messages were persuasive in promoting the rabies exposure prevention behaviour compared with the control condition. In addition, when participants were exposed to the bat-blame messages, more positive beliefs about bats were elicited if the messages included risk–benefit information rather than risk-only information. Conclusions. Our study suggests that public health and wildlife conservation goals can be obtained simultaneously through careful message design. Implications For messages that focus on just the risk information about bats, we suggest at least mentioning anthropogenic factors contributing to the spread of diseases to avoid unintended negative consequences for bat conservation. If messages emphasise bats as the source for spreading diseases, mentioning the benefits of bats may generate more positive beliefs about bats. Both strategies require some modification of the mainstream messages about bats and rabies to meet both public health and conservation goals.